Implementation of the Profile Matching Method in the South Sumatra PON Basketball Player Selection Decision Support System - tya, Aditya tri wulandari; Parjito (P3M Politeknik Negeri Bengkalis, 2025)
Basketball is a popular sport in Indonesia which is ranked third after badminton and football. Basketball is a platform for young people to channel their talents and develop playing skills, especially in South Sumatra Province. In selecting South Sumatra basketball players, an accurate and structured selection process is needed to get quality players. However, player selection is often still carried out by appointing players, which has the potential to cause inaccuracies in player selection. This research implements the Profile Matching method in a decision support system to select player selection based on predetermined criteria, such as physical and technical. The Profile Matching method works by comparing each candidate's profile with a predetermined ideal standard. The calculation is carried out by determining the gap value between the player criteria and the expected standards, then ranking is carried out to obtain accurate and transparent selection results. The research results show that the Profile Matching method is able to increase better accuracy in player selection compared to player appointment selection. In this way, the Profile Matching method helps management make more appropriate decisions and can be a good solution in improving the quality of the South Sumatra basketball team.